Road accident analysis factors - Esmaeeli, H. (2013)
A large number of fatalities on road are occurred by vehicle accident. One of most significant causes of accident on road is increasing car ownership in last decade. The study is conducted to determine a relationship between car ownership and accident rate. The most effective parameters on increasing accident rate in developed countries are studied. This paper investigates a model that forecast the rate of accident on based on previous collected car ownership data. Meanwhile, those parameters can change the rate of car ownership such as income, distance between residential area and work zone, the number of employee over family size and registered car over employee are studied. The study is conducted on based on Australia data and Robust- regression techniques are used to analyse the data. The result shows robust regression reached the most effective coefficient to reduce fatalities on road.